Inquiry-Based Learning Strategy As An Effort To Increase Learning Interest In ISMUBA At MI Muhammadiyah 2 Bandung - Mulyani, Yani; Mu’atawakil, Raihan Muyassar; Hidayat, Abdilah Alam Hernan; Salam, Mochamad Fadlani (PT. Student Rihlah Indonesia, 2025)
This research aims to describe the implementation of the Inquiry-Based Learning (IBL) strategy, analyze teachers' and students' perceptions, and identify supporting and inhibiting factors in increasing learning interest in ISMUBA at MI Muhammadiyah 2 Bandung. A qualitative approach was used, with data collected through in-depth interviews, observations, and documentation involving ISMUBA teachers, students in grades 4–6, and the principal. The results show that IBL was implemented through discussions, case studies, role-playing, and field practice, creating an active, contextual, and enjoyable learning environment. Teachers and students had positive perceptions, feeling more enthusiastic, confident to express opinions, and better understanding Islamic teachings and Muhammadiyah history. Supporting factors include school management support, teacher competence, and a collaborative school culture, while inhibiting factors involve limited modules, varied student characteristics, time constraints, and limited facilities. The novelty lies in applying IBL to ISMUBA by integrating Islamic and Muhammadiyah values, and the implication is to strengthen value-based active learning policies to develop noble-character Muhammadiyah cadres.